The timing of the conscious intention to move - Matsuhashi, Masao (Eur J Neurosci, 2008)
The foundation of modern neuroscience and psychology about intention for action was laid by Libet and his colleagues (Libet, B., et al, Brain 106: 623-42, 1983). They reported the time of awareness of wanting to move to be about 0.2 s before voluntary movement onset. However, despite repeated confirmation of the result, their method has been criticized for its dependence on self-reported timing and subjective memory and the interpretation has been widely debated without general consensus. Here, we show that the mean time of the conscious intention to move was 1.42 seconds before movement, estimated based on subjects’ real-time decision of whether or not there was a thought to move when a tone occurred. This event is after the onset of the Bereitschaftspotential, an electroencephalographic activity preceding voluntary movement, but about one second earlier than the timing of intention reported previously based on subject’s recall. Our result solves some problems of the conventional method, thus giving clearer answer to the controversies. The difference between the conventional result and our result suggests that the perception of intention rises through multiple levels of awareness, starting just after the brain initiates movement.